2008
DOI: 10.1002/iub.95
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of nitrite reductase gene (aniA) and gene product in Neisseria meningitidis isolates: Is aniA essential for meningococcal survival?

Abstract: SummaryThe present study evaluates sequence conservation in the gene coding for nitrite reductase (aniA) and AniA expression from a panel of Neisseria meningitidis isolates. Sequence analysis of the coding region in 19 disease-associated and 4 carrier strains notwithstanding a high degree of sequence similarity showed a number of nucleotide changes, some of which possibly resulted in premature translation termination or function loss. In particular, in one disease-associated strain a 9-residues insertion was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…2D). Results of anaerobic nitrite-dependent growth assays correlated with the differences between meningococci and gonococci in the efficiency of the AniA/NorB systems (28). The US_NmUC isolates yielded substantial growth around the nitrite disk similar to that observed for Ng FA1090 (a representative CNM10 shown in Fig.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…2D). Results of anaerobic nitrite-dependent growth assays correlated with the differences between meningococci and gonococci in the efficiency of the AniA/NorB systems (28). The US_NmUC isolates yielded substantial growth around the nitrite disk similar to that observed for Ng FA1090 (a representative CNM10 shown in Fig.…”
Section: Resultssupporting
confidence: 64%
“…2A). In contrast, meningococci less commonly experience anaerobic conditions, and a functional denitrification pathway is not essential for their survival in the nasopharynx (28,29). Many meningococcal isolates have frame-shift mutations in aniA (29) and cannot grow anaerobically using nitrite as the electron acceptor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that Neisseria meningitidis can respire anaerobically (16,(55)(56)(57). However, AniA is functional in only some strains of N. meningitidis, and it is not required for pathogenesis (63). If an aniA::kan insertion mutant can anaerobically respire through the NorB-mediated reduction of NO, this may also help to explain why biofilm formation is more severely attenuated in the norB::kan mutant (22).…”
Section: Discussionmentioning
confidence: 99%